A bio-anodic filter facilitated entrapment, decomposition and in situ oxidation of algal biomass in wastewater effluent - Mohammadi Khalfbadam, H.; Cheng, K.; Sarukkalige, Priyantha Ranjan; Kaksonen, A.; Kayaalp, A.; Ginige, M. (Elsevier BV, 2016)
This study examined for the first time the use of bioelectrochemical systems (BES) to entrap, decompose and oxidise fresh algal biomass from an algae-laden effluent. The experimental process consisted of a photobioreactor for a continuous production of the algal-laden effluent, and a two-chamber BES equipped with anodic graphite granules and carbon-felt to physically remove and oxidise algal biomass from the influent. Results showed that the BES filter could retain ca. 90% of the suspended solids (SS) loaded. A coulombic efficiency (CE) of 36.6% (based on particulate chemical oxygen demand (PCOD) removed) was achieved, which was consistent with the highest CEs of BES studies (operated in microbial fuel cell mode (MFC)) that included additional pre-treatment steps for algae hydrolysis. Overall, this study suggests that a filter type BES anode can effectively entrap, decompose and in situ oxidise algae without the need for a separate pre-treatment step.